Whole genome sequencing identifies genetic variants associated with co-trimoxazole hypersensitivity in Asians - Wang, Chuang-Wei; Tassaneeyakul, Wichittra; Chen, Chun-Bing; Chen, Wei-Ti; Teng, Yu-Chuan; Huang, Cheng-Yang; Sukasem, Chonlaphat; Lu, Chun-Wei; Lee, Yun-Shien; Choon, Siew-Eng; Nakkam, Nontaya; Hui, Rosaline Chung-Yee; et al. (Journal of allergy and clinical immunology, 2021)
Co-trimoxazole, a sulfonamide antibiotic, is used to treat a variety of infections worldwide, and it remains a common first-line medicine for prophylaxis against Pneumocystis jiroveci pneumonia. However, it can cause severe cutaneous adverse reaction (SCAR), including Stevens-Johnson syndrome, toxic epidermal necrolysis, and drug reaction with eosinophilia and systemic symptoms. The pathomechanism of co-trimoxazole–induced SCAR remains unclear. We aimed to investigate the genetic predisposition of co-trimoxazole–induced SCAR. We conducted a multicountry case-control association study that included 151 patients with of co-trimoxazole–induced SCAR and 4631 population controls from Taiwan, Thailand, and Malaysia, as well as 138 tolerant controls from Taiwan. Whole-genome sequencing was performed for the patients and population controls from Taiwan; it further validated the results from Thailand and Malaysia. The whole-genome sequencing study (43 case patients vs 507 controls) discovered that the single-nucleotide polymorphism rs41554616, which is located between the HLA-B and MICA loci, had the strongest association with co-trimoxazole–induced SCAR (P = 8.2 × 10−9; odds ratio [OR] = 7.7). There were weak associations of variants in co-trimoxazole–related metabolizing enzymes (CYP2D6, GSTP1, GCLC, N-acetyltransferase [NAT2], and CYP2C8). A replication study using HLA genotyping revealed that HLA-B∗13:01 was strongly associated with co-trimoxazole–induced SCAR (the combined sample comprised 91 case patients vs 2545 controls [P = 7.2 × 10−21; OR = 8.7]). A strong HLA association was also observed in the case patients from Thailand (P = 3.2 × 10−5; OR = 3.6) and Malaysia (P = .002; OR = 12.8), respectively. A meta-analysis and phenotype stratification study further indicated a strong association between HLA-B∗13:01 and co-trimoxazole–induced drug reaction with eosinophilia and systemic symptoms (P = 4.2 × 10−23; OR = 40.1). This study identified HLA-B∗13:01 as an important genetic factor associated with co-trimoxazole–induced SCAR in Asians.